2021
DOI: 10.1007/s10903-021-01309-1
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Enhance Retention in a Cohort Study Among Adults of Turkish Descent Living in Berlin

Abstract: Retention is important for statistical power and external validity in long-term cohort studies. The aims of our study were to evaluate different retention strategies within a cohort study of adults of Turkish descent in Berlin, Germany, and to compare participants and non-participants. In 2011–2012, a population-based study was conducted among adults of Turkish descent to primarily examine recruitment strategies. 6 years later, the participants were re-contacted and invited to complete a self-report questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Participation proportions also vary considerably across social groups [ 1 , 23 , 63 ]. For instance, participation proportions in surveys and genomic cohort studies have been found to be lower for men [ 47 ] and ethnic minorities [ 44 61 37 20 ] or migrant populations [ 63 74 ]. Participants in longitudinal research are more likely to be educated to at least undergraduate level [ 11 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participation proportions also vary considerably across social groups [ 1 , 23 , 63 ]. For instance, participation proportions in surveys and genomic cohort studies have been found to be lower for men [ 47 ] and ethnic minorities [ 44 61 37 20 ] or migrant populations [ 63 74 ]. Participants in longitudinal research are more likely to be educated to at least undergraduate level [ 11 25 ].…”
Section: Introductionmentioning
confidence: 99%